Effect of Refractance Window on dehydration of osmotically pretreated apple slices: Color and texture evaluation. (6th November 2019) - Hernández, Yossebann; Ramírez, Cristian; Moreno, Jorge; Núñez, Helena; Vega, Oscar; Almonacid, Sergio; Pinto, Marlene; Fuentes, Lida; Simpson, Ricardo
Abstract: The objective of this research was to explore the advantages of apple slices dehydration (cv. Granny Smith) using a Refractance Window (RW) with and without osmotic dehydration as pretreatment and compared with conventional hot‐air drying considering the quality attributes such as color and texture. For pretreatment, the apple slices were osmotically dehydrated and coupled to a moderate electric field (9.3 V/cm) using a sucrose solution (45°Brix) at 40°C until an A w = 0.95 was achieved. Then, apple slices (with and without pretreatment) were dehydrated using RW at 55, 75, and 95°C and compared with conventional hot‐air drying at 55°C as a control. The results showed that with dehydration using RW, both with and without pretreatment at 95°C, it was possible to achieve a similar quality of apple slices when compared with conventional hot‐air drying at 55°C, but with a significant reduction in processing time. Additionally, the dehydration process using RW presented anomalous diffusion behavior on apple slices with an α  > 1. Practical applications: Refractance Window (RW) is a technology used for dehydration of fruit and vegetables slices and pulp based on the refractance properties of wet materials. RW has reported promising results in processing time reduction as compared with conventional dehydration methods. In addition, the quality of the end products by RW is higher as compared with conventional drying methods. In this research, we have showed that the final product (dehydrated apple slices) using RW attained quality values (color and texture) similar to those obtained with osmotic dehydration (OD) coupled with moderate electric field (MEF)/hot‐air drying. However, the time spent by RW (50 min) was much lower than OD coupled with MEF/hot‐air drying (240 min). Then, the main advantage of RW is the capacity to dehydrate fruit and vegetables materials using temperatures around 100°C, which allow both, reduce processing time and also attain high‐quality retention.